HUBUNGAN MANAJEMEN WAKTU DENGAN PROKRASTINASI AKADEMIK SISWA KELAS XI DI SMAN 6 TANGERANG - Zahira Fikra Fakhrina; Titik Haryati (Jurnal Ilmiah Global Education, 2023)
Time management was managing time by identifying the needs and desires of students and arranging them in order of importance, while academic procrastination was delaying starting or completing work in the field of learning. This study aimed to determine the level of time management, the level of academic procrastination and the relationship between time management and academic procrastination. This study used a quantitative approach with a correlational research design. The population in this study numbered 384 with 80 samples. Data collection techniques used questionnaires and sampling using proportional random sampling method with samples taken randomly without regarded to strata in the population. This study used data analysis, namely descriptive analysis. The result of this study indicated that there was a significant negative relationship between time management and student procrastination with a value of -0.694. The result also showed that the higher level of student time management, so that the lower level of student academic procrastination.